SPORT CYBERPSYCHOLOGY - Hurley, Olivia ([S.l.] : ROUTLEDGE, 2024)
The new edition of Sport Cyberpsychology is the only textbook in this field that provides a detailed overview of theories, concepts and research findings specifically related to the discipline of sport cyberpsychology. Post-pandemic, this new edition explores the vast psychological impact technology has on athletes' thoughts, emotions and preparations for their sport, as well as the role technology plays in sport consulting, officiating and social interactions. It covers topics that include performance-enhancing technologies, social media use by athletes and sport personnel (e.g., sport officials) and the role of technology in sport psychology consulting. Problematic behaviours athletes may encounter or engage in within the online world, such as their experiences with cyberbullying and online gambling are alsodiscussed. This second edition includes a review of the latest esports research and activities that are gaining global popularity. The final chapter presents some new research horizons in the field of sport cyberpsychology. The book includes a range of helpful features including case studies, open-ended discussion questions, suggestions for future research studies and extensive reference lists. Accessibly written, this edition of Sport Cyberpsychology offers a one-stop, engaging resource for students and instructors alike. It is important reading for students of sport psychology, cyberpsychology, sport coaching, sport officiating and sport technology, as well as coaches, traditional athletes, esports athletes, sport scientists and performers in areas such as dance, the arts, the military and medicine.
Keywords: Sports -- Technological innovations -- Psychological aspects; Performance technology -- Psychological aspects; Athletes -- Psychology; SPORTS & RECREATION / Sports Psychology; PSYCHOLOGY / Applied Psychology